(untitled) (Archaeologia Adriatica, 2022)
The historical background of Ugljan is closely related to the development of Zadar as a nearby urban center. Centuriation remains, recorded across the entire island, are particularly significant, as well as ancient residential and agricultural hubs (villae rusticae), the one in Muline being the most renowned. One such complex was recognized in the Preko settlement, while its various adaptations testify to life continuity from the 2nd to the early 6th century. A recent archaeological field survey in Preko enabled the identification of an unpublished Roman funerary inscription at the cemetery of the church of Our Lady of the Rosary. The paper presents its reading and interpretation within the historical panorama of the island. The form and characteristics of the inscription date to the period between the late 1st and the first half of the 2nd century. The same cemetery yielded a late antique sarcophagus with a gable roof that, alongside an impost capital with an engraved cross on the front of the present-day church, suggests a possibility of the presence of an earlier early Christian church. It was probably dedicated to St Andrew, as indicated by a hagiotoponym of this region, used until the Early Modern Period. The present-day church of Our Lady of the Rosary, built in the 18th century is as well, decorated by a Roman relief, used as an architrave of the front door. All the aforementioned elements enable noticing a trend of significant interest in the Preko, from the Roman period to the present, with an especially interesting phase of Late Antiquity.